2019
DOI: 10.3390/en12050950
|View full text |Cite
|
Sign up to set email alerts
|

Forecasting the Carbon Price Using Extreme-Point Symmetric Mode Decomposition and Extreme Learning Machine Optimized by the Grey Wolf Optimizer Algorithm

Abstract: Due to the nonlinear and non-stationary characteristics of the carbon price, it is difficult to predict the carbon price accurately. This paper proposes a new novel hybrid model for carbon price prediction. The proposed model consists of an extreme-point symmetric mode decomposition, an extreme learning machine, and a grey wolf optimizer algorithm. Firstly, the extreme-point symmetric mode decomposition is employed to decompose the carbon price into several intrinsic mode functions and one residue. Then, the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 38 publications
(19 citation statements)
references
References 57 publications
0
18
0
1
Order By: Relevance
“…Sun et al [17] applied the particle swarm optimization the extreme value learning machine for carbon emission prediction research. Zhou et al [27] used Grey Wolf Optimizer (GWO) binding to the ELM model to predict carbon prices, which indicated that the predictive precision of the optimized ELM model outperformed the single ELM. Sun and Zhang [15] applied the extreme learning machine optimized by the adaptive whale optimization algorithm to carbon price prediction, and the results verified that the optimized ELM performance is more accurate than before the optimization.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Sun et al [17] applied the particle swarm optimization the extreme value learning machine for carbon emission prediction research. Zhou et al [27] used Grey Wolf Optimizer (GWO) binding to the ELM model to predict carbon prices, which indicated that the predictive precision of the optimized ELM model outperformed the single ELM. Sun and Zhang [15] applied the extreme learning machine optimized by the adaptive whale optimization algorithm to carbon price prediction, and the results verified that the optimized ELM performance is more accurate than before the optimization.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Zhang et al (2019) used ELM to predict apoptosis protein subcellular localization. Zhou et al (2019) used ELM to forecast the carbon price. Zhu et al (2019) predicted the daily water temperature for rivers by the ELM method.…”
Section: The Elm Modelmentioning
confidence: 99%
“…The gradient descent strategy used in the training of traditional neural networks may cause defects such as slow convergence, the disappearance of gradients, and sensitivity to parameter settings. The unique design structure of ELM gives it the advantages of fast convergence, fewer parameters to be adjusted, and strong generalization ability, which makes it widely used in research in various fields [34].…”
Section: Extreme Learning Machine (Elm)mentioning
confidence: 99%